Utilization of chicken (Gallus domesticus0 egg shells as pultry feed. - Deocampo, Ma. Rita Louella D.
One of the major problems that impede further development of the Philippine poultry industry is the lack of continous supply of quality feed ingredients and mixed feeds. This research aims to test the efficiency of egg shells of chicken, classified as Gallus domesticus, as an additive to the poultry feed., Feeding experiments were conducted on five poultry lots. Each lot was given a different ratio of the egg shell and prepared basal ration. The efficiency of the ration given, was based on the weekly average gain in weight of the poultry lots. Results showed that the lot fed with 25 egg shell and 75 basal ration, gave the highest return above feed costs. However, the lot which was feed with 100 egg shell gave an 80 rate or mortality after the eight week period. No biological or physiological tests were involved in this study, however, symptoms of ill health were noted in the lot fed with the 100 egg shell. Analysis of Variance (ANOVA) for the percentage of growth rate and weekly average gain in weights of the first four lots showed no significant differences. Proximate chemical analysis of the egg shell showed that it contains (average): 1.2 moisture, 66.44 ash, 1.28 fat, 24.22 fiber, 3.38 protein, 4.48 nitrogen-free extract, 98.5 calcium and 0.799magnesium. On the other hand, analysis of the basal ration exhibited 12.8 moisture, 9.96 ash, 4.05 fat, 8.38 fiber, 21.16 protein, 56.46 nitrogen-free extract, 0.2& calcium and 0.29 magnesium. Phosphorous was not tested quantitatively due to the malfunctioning of the spectrophotometer, though qualitatively it was proven to be present in both the egg shell and the basal ration. It is concluded from this research that the egg shell can be used as a good additive at a 75 BR-25 ES ratio, since a high return over feed costs can be obtained with this combination. It is recommended that chemical tests of the chicken tissues and further mineral assay of the egg shell and basal ration be conducted.